2000
DOI: 10.1093/jn/130.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Grape Juice, But Not Orange Juice or Grapefruit Juice, Inhibits Human Platelet Aggregation

Abstract: Coronary artery disease is responsible for much mortality and morbidity around the world. Platelets are involved in atherosclerotic disease development and the reduction of platelet activity by medications reduces the incidence and severity of disease. Red wine and grapes contain polyphenolic compounds, including flavonoids, which can reduce platelet aggregation and have been associated with lower rates of cardiovascular disease. Citrus fruits contain different classes of polyphenolics that may not share the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
150
0
7

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(164 citation statements)
references
References 26 publications
5
150
0
7
Order By: Relevance
“…35 Nevertheless, several recent reports have suggested that increased dietary flavonoid consumption may inhibit platelet activation and function in humans. 36,37 Rein and colleagues 36 randomized 30 healthy volunteers to either cocoa, a caffeine-containing control beverage, or water and found that cocoa consumption suppressed ADP-and epinephrine-stimulated platelet activation acutely and had an aspirinlike effect on primary hemostasis as measured with a platelet function analyzer. Cocoa is high in flavonoids, especially catechins, 38 and has been shown by Rein and colleagues to decrease plasma markers of oxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Nevertheless, several recent reports have suggested that increased dietary flavonoid consumption may inhibit platelet activation and function in humans. 36,37 Rein and colleagues 36 randomized 30 healthy volunteers to either cocoa, a caffeine-containing control beverage, or water and found that cocoa consumption suppressed ADP-and epinephrine-stimulated platelet activation acutely and had an aspirinlike effect on primary hemostasis as measured with a platelet function analyzer. Cocoa is high in flavonoids, especially catechins, 38 and has been shown by Rein and colleagues to decrease plasma markers of oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…The first study 36 assessed markers of platelet activation and function, and the second study 37 measured whole-blood aggregation. In the present study, we assessed ex vivo platelet aggregation in plateletrich plasma, a method that has been shown to relate to CAD mortality 40 and previous myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, grape juice also inhibited protein kinase C and spared cellular antioxidants. Red wine has more potent antiplatelet effects than white wine (66) and these effects are not seen with other beverages, such as orange juice and grapefruit juice, which contain other antioxidants (67).…”
Section: Epidemiologymentioning
confidence: 99%
“…For example, in studies conducted with grapes and grape juice, clinical trials have demonstrated decreased platelet aggregation (PaceAsciak et al, 1996;Folts, 1998;Keevil et al, 2000;Freedman et al, 2001), improved endothelial function (Stein et al, 1999;Coimbra et al, 2005;Lekakis et al, 2005), reduced blood pressure (Park et al, 2004), and positive influences on biomarkers such as HDL, LDL, apo-B, and MCP-1 (Hansen et al, 2005;Zern et al, 2005;Castilla et al, 2006). Accordingly, it is apparent that grape consumption can modulate several factors that are associated with health benefits.…”
Section: Introductionmentioning
confidence: 99%